Kerja Sama Internasional dalam Mengatasi Dampak Negatif Cuaca Antariksa - Wibowo, Antonia Rahayu Rosaria (Andalas Institute of International Studies UNAND, 2022)
Space weather refers to the dynamic condition of the sun and space environment and also its impacts on the technology system. Space weather influences human life because human depends on space assets like communication satellite and navigation. If there is a problem related to space weather, humans on Earth will feel it. This paper answers a question on how is international cooperation to overcome the negative impacts of space weather. The aim of this paper is to elaborate and analyze international cooperation to overcome the negative impacts of space weather by using international organization and cooperation theory. This paper used a descriptive method by describing the negative impacts of space weather and the international cooperation that has been conducted to overcome them. International Space Weather Initiative (ISWI), International Space Environment Service (ISES), and Pan-European Consortium for Aviation Space Weather User Services (PECASUS) were discussed in this paper. The analysis shows that ISWI, ISES, and PECASUS emerged due to awareness among countries regarding the negative impacts of space weather. Those international cooperation efforts have their respective duties and functions. However, all three are associative, contribute to human life in the future, and are able to control the behavior of member countries.